2015
DOI: 10.1007/s11356-015-4633-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the importance of litter as a co-substrate for MCPA dissipation in an agricultural soil

Abstract: Environmental controls of 2-methyl-4-chlorophenoxyacetic acid (MCPA) degradation are poorly understood. We investigated whether microbial MCPA degraders are stimulated by (maize) litter and whether this process depends on concentrations of MCPA and litter. In a microcosm experiment, different amounts of litter (0, 10 and 20 g kg(-1)) were added to soils exposed to three levels of the herbicide (0, 5 and 30 mg kg(-1)). The treated soils were incubated at 20 °C for 6 weeks, and samples were taken after 1, 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Therefore, we used experimental data from previous studies to evaluate models’ performance. Short-term experiments showed that both 2,4-D and MCPA are readily degradable compounds which do not persist in soil. Some experiments have reported no 2,4-D and MCPA residues or residues below detection limit after 1 to 5 weeks. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used experimental data from previous studies to evaluate models’ performance. Short-term experiments showed that both 2,4-D and MCPA are readily degradable compounds which do not persist in soil. Some experiments have reported no 2,4-D and MCPA residues or residues below detection limit after 1 to 5 weeks. , …”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the effects these herbicides and organic residues have on the various groups of soil microorganisms when they are applied jointly. Most of the studies on soil microbial response to pesticides and organic residues have been assessed at laboratory or greenhouse scale [6,14,[22][23][24][25], but only a few assays have been performed at field scale [13,19]. Moreover, only one study has been found in the literature that refers to the impact on soil microbial activity of the combined application of the herbicide chlorotoluron with organic residues under field conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been indicated a significant early impact and a relevant late impact on the bacterial community when the application of pethoxamid and glyphosate to soil was carried out (Valverde et al, 2014). Saleh et al (2016) have reported signs of toxic effects on soil bacteria at high herbicide (MCPA) concentrations. Karpouzas et al (2014) have reported the inhibitory effects of nicosulfuron on Actinobacteria at rates 20 times higher than the recommended ones.…”
Section: Phospholipid Fatty Acid Profile Analysismentioning
confidence: 99%